2016
DOI: 10.1016/j.psyneuen.2016.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Chronic social isolation enhances reproduction in the monogamous prairie vole (Microtus ochrogaster)

Abstract: Chronic stressors are generally considered to disrupt reproduction and inhibit mating. Here we test the hypothesis that a chronic stressor, specifically social isolation, can facilitate adaptive changes that enhance/accelerate reproductive effort. In general, monogamous species display high levels of prosociality, delayed sexual maturation, and greater parental investment in fewer, higher quality offspring compared with closely related polygynous species. We predicted that chronic social isolation would promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 59 publications
(92 reference statements)
1
6
0
Order By: Relevance
“…However, our data are consistent with a recent study in California mice showing that social isolation enhances cell survival and proliferation in the hippocampus (Ruscio et al, 2015). Chronic social isolation in prairie voles also increase estrogen receptors in the medial amygdala (MEA) and the bed nucleus of stria terminalis (BST) of males, decrease corticotropin-releasing hormone (CRH) receptor type 1 but increase CRH receptor type 2 in the hippocampus (PournajafiNazarloo et al, 2009;Perry et al, 2016). Given that CRH-R1 and CRH-R2 have been found to differentially modulate dendritic growth of hippocampal neurons (Sheng et al, 2012), it is possible that these receptors along with estrogen receptors may mediate alterations of the hippocampal neuronal structure in response to moderate environmental disruptions experienced during offspring development of monogamous species.…”
Section: Discussionsupporting
confidence: 92%
“…However, our data are consistent with a recent study in California mice showing that social isolation enhances cell survival and proliferation in the hippocampus (Ruscio et al, 2015). Chronic social isolation in prairie voles also increase estrogen receptors in the medial amygdala (MEA) and the bed nucleus of stria terminalis (BST) of males, decrease corticotropin-releasing hormone (CRH) receptor type 1 but increase CRH receptor type 2 in the hippocampus (PournajafiNazarloo et al, 2009;Perry et al, 2016). Given that CRH-R1 and CRH-R2 have been found to differentially modulate dendritic growth of hippocampal neurons (Sheng et al, 2012), it is possible that these receptors along with estrogen receptors may mediate alterations of the hippocampal neuronal structure in response to moderate environmental disruptions experienced during offspring development of monogamous species.…”
Section: Discussionsupporting
confidence: 92%
“…This study, which remains among few of its kind in a vertebrate, showed strong evidence that phenotypic divergence between the populations is explained by divergence in ERα distribution. Levels of ERα in the medial amygdala depend, to a degree, on environmental factors (Perry et al, 2016) but may also be modulated by regulatory variation as described above in Section 4. To further connect gene sequence with behavior in voles, juncos, and other behaviorally diverging populations, regulatory variation in sex steroid receptors should be identified and its ability to alter gene expression tested in vitro.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Any kind of stress can affect brain function by making long-term changes in the nervous system. There is evidence that SIS experience in early life is associated with depression and anxiety behaviors (22).…”
Section: Discussionmentioning
confidence: 99%